The Influence of Shopee's Brand Awareness and Brand Image on Consumer Purchase Decisions - Audia Narda Nismara (International Journal Administration, Business & Organization, 2022)
The purpose of this research is to determine and analyze the influence of Shopee marketplace's brand awareness and brand image on consumer purchasing decisions. The research method used was quantitative descriptive. The population of this study consists of all students of Politeknik Negeri Bandung who are consumers of Shopee. Data was collected through the distribution of questionnaires to 110 respondents. Data analysis involved descriptive analysis, multiple linear regression, validity and reliability tests, coefficient of determination, t-test, and F-test. The results of the study indicate that brand awareness and brand image of the Shopee marketplace have a significant positive influence on consumer purchasing decisions. The contribution of brand awareness and brand image of Shopee to consumer purchasing decisions reaches 66.1%. It can be concluded that brand awareness and brand image are important factors in influencing consumer purchasing decisions in the Shopee marketplace.